2009
DOI: 10.1074/jbc.m109.009258
|View full text |Cite
|
Sign up to set email alerts
|

The C-Glycosylation of Flavonoids in Cereals

Abstract: Flavonoids normally accumulate in plants as O-glycosylated derivatives, but several species, including major cereal crops, predominantly synthesize flavone-C-glycosides, which are stable to hydrolysis and are biologically active both in planta and as dietary components. An enzyme (OsCGT) catalyzing the UDPglucose-dependent C-glucosylation of 2-hydroxyflavanone precursors of flavonoids has been identified and cloned from rice (Oryza sativa ssp. indica), with a similar protein characterized in wheat (Triticum ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
262
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 265 publications
(280 citation statements)
references
References 44 publications
9
262
1
2
Order By: Relevance
“…4C). In fact, the MS/MS spectrum is consistent with those reported for the OsCGT reaction products formed in vitro from 2-hydroxyflavanones (Brazier-Hicks et al, 2009). When the double transformant extracts were acid treated, the C-glucosyl-2-hydroxynarigenin peak was not detected by LC-MS analysis.…”
Section: Transgenic Arabidopsis Overexpressing Cyp93g2 or Coexpressinsupporting
confidence: 72%
See 3 more Smart Citations
“…4C). In fact, the MS/MS spectrum is consistent with those reported for the OsCGT reaction products formed in vitro from 2-hydroxyflavanones (Brazier-Hicks et al, 2009). When the double transformant extracts were acid treated, the C-glucosyl-2-hydroxynarigenin peak was not detected by LC-MS analysis.…”
Section: Transgenic Arabidopsis Overexpressing Cyp93g2 or Coexpressinsupporting
confidence: 72%
“…2-Hydroxyflavanones, not flavanones or flavones, were identified to be substrates for C-glucosylation Franz, 1987, 1988). Consistent with this, the rice C-glucosyltransferase OsCGT was recently demonstrated to catalyze the UDP-Glc-dependent C-glucosylation of 2-hydroxyflavanone substrates (Brazier-Hicks et al, 2009). In addition, dehydratase activities that preferentially converted 2-hydroxyflavanone C-glucosides to 6C-glucosylflavones were demonstrated in both rice and wheat extracts (Brazier-Hicks et al, 2009).…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…The flavone biosynthesis pathway is shown according to Zhou et al (2008), Corté s-Cruz et al (2003, and Lam et al (2014Lam et al ( , 2015. The enzymes involved in the metabolic route via F2H toward apigenin and luteolin conjugates has been described in rice, wheat, and buckwheat (Fagopyrum esculentum;Brazier-Hicks et al, 2009;Du et al, 2010). The biosynthetic routes via HCT and HQT have been described in switchgrass (Escamilla-Treviñ o et al, 2014) and suggested to be present in maize (Corté s-Cruz et al, 2003).…”
mentioning
confidence: 99%